Biobased nanocomposites for packaging applications — synthesis using melt extrusion of poly (lactic acid), poly (butylene succinate) and/or starch blended with natural nanofillers - Xu, Jingwen (Kansas State University, 2015)
There is a renewed focus on biodegradable polymers in packaging applications due to environmental concerns associated with conventional plastics. Melt extrusion was used to synthesize nanocomposites from poly (lactic acid) (PLA) or poly (butylene succinate) (PBS) blended with natural nanofillers — chitin whiskers (CHW, 1-5%), nanocrystalline cellulose (NCC, 1-5%) or lignin-coated nanocrystalline cellulose (LNCC, 3%). Transmission electron microscopy and x-ray diffraction indicated that the natural nanofillers were uniformly dispersed in the polymer matrix. For PLA based nanocomposites, differential scanning calorimetry showed a decrease in change of heat capacity at glass transition (ΔCp) with increased nanofiller addition, indicating greater confinement of polymer chains. For PBS based nanocomposites, nanofillers acted as nucleating agents and promoted recrystallization of polymer as reflected in increase of degree of crystallinity (Xc) from 65.9-66.8 to 75.6%. By addition of NCC and CHW, tensile strength (TS) of PLA based films increased from 50.2 MPa to 70.9 MPa and 52.1 MPa, respectively, while TS of PBS increased from 23.2-24.9 MPa to 32.9 MPa and 43.6 MPa, respectively. Elongation at break (E%) of nanocomposite films ranged from 9.1 to 15.3, and in general decreased with addition of nanofillers. LNCC did not significantly improve mechanical properties of PBS and PLA films. Additionally, 3% NCC addition reduced oxygen transmission rate (OTR) of PLA from 209.9 to 180.8 cc/m[superscript]2/day, which further reduced to 109.3 cc/m[superscript]2/day by adding compatibilizer methylene diphenyl diisocyanate (MDI, 4%). Water vapor transmission rate (WVTR) of PLA also reduced from 44.4 to 28.6 g/m[superscript]2/day with 3% NCC and 4% MDI addition. Similarly OTR and WVTR of PBS decreased from 737.7 to 280 cc/m[superscript]2/day and 83.8 to 49.4 g/m[superscript]2/day, respectively with 3% NCC. Use of 4% MDI further reduced OTR and WVTR to 23.8 cc/m[superscript]2/day and 30.8 g/m[superscript]2/day, respectively. Use of starch can potentially reduce the costs of bio-based nanocomposites films. Up to 40% starch was incorporated during synthesis of PLA and NCC nanocomposites using solution mixing method. Addition of starch decreased TS from 35.8 MPa to 18.4 MPa and E% from 8.3% to 6.0%. Use of NCC (1%) and MDI (4%) improved the mechanical properties to a certain extent.
Keywords: Packaging AppliacationsBiobased Nanocomposites; Agriculture, General (0473)